Content matters : a disciplinary literacy approach to improving student learning - McConachie, Stephanie M., 1946-; Petrosky, Tony; Resnick, Lauren B. (Jossey-Bass education series., 2010)
An authoritative guide for improving teaching, learning, and literacy in content area classrooms. This book introduces teachers to the Disciplinary Literacy instructional framework developed by the Institute for Learning, University of Pittsburgh. Grounded in the Principles of Learning developed by acclaimed educator Lauren Resnick, the framework is designed to prepare students, grades 6 and up, to master the rigorous academic content learning required for college success. Unlike 'generic' teaching models, the framework is specifically tailored for each of the content disciplines.